ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP JEMAAH UMROH DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) PT. FIRST ANUGERAH KARYA WISATA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR : 105/Pdt.SUS PKPU/2017/PN.Niaga.Jkt.Pst) - VERNANDO VERNANDO (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Sunarmi, SH, MHum2. Prof. Dr. Hasim purba, SH, MHum3. Dr. Dedi Harianto, SH, MHumThe candidates of umrah pilgrims (Islamic pilgrimage to Mecca, Saudi Arabia) who had registered and made full payment for umrah promo in 2017 through letter of PT. First Anugerah Karya Wisata should have left in June, 2017, but it was unilaterally postponed and they were offered options to take another schedule or to get refund. The research employs normative legal research method which studies library collections or secondary data consisting of primary, secondary and tertiary legal materials. The data are collected from analyzing documents and scientific books to gain theoretical basis such as positive law in accordance with the research object. The instrument used to collect the data is document. The analysis is made by applying qualitative technique. The results demonstrate that having the debtor with PKPU requested for reconciliation plan in a proposal such as rescheduling, debt acknowledgment for the unverified and unpaid past due debt by the creditor with PKPU is the form of the legal protection for the creditor with PKPU.Keywords: Legal Protection, Umrah Pilgrims, a Suspension of Debt Payment Obligation, PT. First Anugerah Karya Wisata